Os caminhos argumentativos para a unidade das virtudes no Protágoras de Platão: uma perspectiva ética - Albuquerque, João Victor (2018)
The present text will address the theme about the unity of virtue in Plato's Protagoras dialogue. The question that will be analyzed is limited to understanding the argumentative paths used by Socrates for the refutation of the sophist Protagoras with his perspective of unity of virtue. Another point that will be approached as a reflection of this analysis will be the understanding of the unity thesis between the virtues - justice, piety, courage, wisdom and wisdom - that the philosopher establishes.